(untitled) (Western European Journal of Medicine and Medical Science, 2026)
Anemia is one of the most significant nutritional deficient conditions affecting various social groups and levels of socio-economic development. With a variety of causes, anemia can be of nutritional origin (iron, folic acid and vitamin B12 deficiency), hereditary (thalassemia, sickle cell anemia), due to environmental factors (lead), infectious (malaria), socio-economic (low maternal education, insufficient family income), related to demographic characteristics (age, gender), malabsorption (achlorhydria), autoimmune processes (hemolytic anemia) or chronic diseases (oncological pathology). Despite the widespread occurrence of iron in nature, its deficiency in humans is extremely common and is the leading cause of anemia worldwide. Iron deficiency anemia (IDA) is a global public health problem that is common in all countries and has serious health consequences, especially in pregnant women, infants, young children, and adolescents who are at increased risk for iron deficiency [1]. Iron enters the body in heme (animal) and non-heme (plant) forms; at the same time, heme iron has a higher bioavailability, which makes people who follow a vegetarian diet more vulnerable to the development of iron deficiency